Gideon's gift : a novel - Kingsbury, Karen (Kingsbury, Karen. Red gloves series., 2002)
"Holiday tale of a man who has lost all hope, an irrepressible child suffering from a terrible illness and the one small act of love and faith that will give them both the greatest gift of all."--Jacket.